Considerations for Screening Live Kidney Donors for Endemic Infections: A Viewpoint on the UNOS Policy. Issue 5 (17th March 2014) - Levi, M. E.; Kumar, D.; Green, M.; Ison, M. G.; Kaul, D.; Michaels, M. G.; Morris, M. I.; Schwartz, B. S.; Echenique, I. A.; Blumberg, E. A.
Abstract : In February 2013, the Organ Procurement and Transplantation Network mandated that transplant centers perform screening of living kidney donors prior to transplantation for Strongyloides, Trypanosoma cruzi and West Nile virus (WNV) infection if the donor is from an endemic area. However, specific guidelines for screening were not provided, such as the optimal testing modalities, timing of screening prior to donation and the appropriate selection of donors. In this regard, the American Society of Transplantation Infectious Diseases Community of Practice, together with disease‐specific experts, has developed this viewpoint document to provide guidance for the testing of live donors for Strongyloides, T. cruzi and WNV infection, specifically identifying at‐risk populations and testing algorithms, including advantages, limitations and interpretation of results. Abstract : In response to the requirement for live kidney donor screening for Chagas disease, strongyloidiasis, and West Nile virus by the Organ Procurement and Transplantation Network, the Transplant Infectious Diseases Community of Practice provides specific testing guidelines. (Also see case report by Le et al on page 1199.)